Simultaneous removal of chlorite and contaminants of emerging concern under UV photolysis: Hydroxyl radicals vs. chlorate formation. (15th February 2021) - Wang, Jue; Wu, Yangtao; Bu, Lingjun; Zhu, Shumin; Zhang, Weiqiu; Zhou, Shiqing; Gao, Naiyun
Highlights: UV photolysis has the ability to simultaneously remove CECs and ClO2 ‒ . Reactive chlorine species are the main contributor to CBZ degradation. The yields of Cl ‒ and ClO3 ‒ are affected by the dosage of ClO2 ‒ . ClO3 ‒ formation has a strong correlation with k H O / R in UV/ClO2 ‒ system. Abstract: It is well known that using chlorine dioxide (ClO2 ) as a disinfectant inevitably produces a common disinfection byproducts chlorite (ClO2 ‒ ). In this study, we found that UV photolysis after ClO2 disinfection can effectively eliminate both ClO2 ‒ and contaminants of emerging concern (CECs). However, the kinetic mechanisms of UV/ClO2 ‒ process destructing CECs, as well as transformation of ClO2 ‒ in UV/ClO2 ‒ system are not clear yet. Therefore, we systematically investigated the UV/ClO2 ‒ system to assist us appropriately design this process under optimal operational conditions. In this work, we first investigated the impact of water matrix conditions (i.e., pH, bicarbonate and natural organic matter (NOM)) and ClO2 ‒ dosage on the UV/ClO2 ‒ process. We found that bicarbonate and NOM have inhibition effects, while lower pH and higher ClO2 ‒ dosage have enhancement effects. Besides, hydroxyl radical (HO ) and reactive chlorine species (RCS) are generated from UV/ClO2 ‒ system, and RCS are main contributors to CBZ degradation. Then we proposed a possible degradation pathway of CBZ based on the determined products from experiments. Additionally, we found that photolysis of ClO2 ‒ resulted in the generation of chloride (Cl ‒ ) and chlorate (ClO3 ‒ ). As the ClO2 ‒ dosage increases, the yield of ClO3 ‒ increased while that of Cl ‒ decreased. Finally, we elucidated the second order rate constant of the target organic compound with HO has a strong correlation with the formation of ClO3 ‒ . Graphical abstract: Image, graphical abstract